Teori-Teori Transorientasional dalam Psikologi Sosial - Juneman, Juneman (Bina Nusantara University, 2011)
The author discusses the recognition of social judgment theory, descriptive model of social response, and role theory as transorientational social psychological theories, criticism in this field as well as their application in everyday’s life.